Factors Related To Anxiety And Depression In Patients With Inflammatory Bowel Disease: Influence Of Emotions On Intestinal Diseases - dos Santos, Carlos Henrique Marques; Galindo, Amanda Cristine Alcântara; da Silva, Bárbara Alencar; Dantas, Camila Rodrigues; Guilherme, Isadora Albuquerque de Araujo; Gomes, José Elias Basmage Nunes; Dallacqua, Kayque Michel; de Souza, Mariana Pereira; Senna, Patricia Szlachta (Seven Editora, 2023)
DOI: https://doi.org/10.56238/colleinternhealthscienv1-093